Melt-state dynamic pressure engineered Polybutene-1 with form I crystals. (21st September 2022) - Wei, Xingzhao; Qu, Yuntao; Jiang, Haowei; Huang, Zhao-Xia; Qu, Jin-Ping
Abstract: Controlling the crystalline structure of semi-crystalline polymers is a primary topic for the entire polymer society. Among all investigations in this area, polybutene-1(PB-1) attracts an avalanche of attentions due to its essential feature of conventionally crystallizing into the kinetically favored metastable form II from melts, and then slowly transforms into the thermodynamically stable form I. Although enormous reports studied how to accelerate the transformation of PB-1 from form II to form I, it is still unable to directly obtain high-content form I crystals from pure PB-1 melts, which leads to unavoidable volume shrinkage issue. Herein, we report a novel dynamic pressure engineering (DPE) technique, which can directly induce predominated form I crystals formation from pure PB-1 melts. The initial form I proportion of DPE-processed samples surpasses 60% by FTIR, which is the first report of obtaining PB-1 with predominated form I crystals from pure PB-1 melts. Based on experimental investigations, the novel dynamic pressure induced form I PB-1 formation mechanism has been proposed, which is closely related to the relaxation time of the loose packed (11/3) conformation. Ultimately, this work not only provides a novel technique that can fabricate PB-1 with predominated form I crystals in a simple, highly efficient and low-cost way, but also reveals the essential role of melt-state pressure on the controlled crystallization of polymers. Graphical abstract: Image 1 Highlights: In this work, we report a novel dynamic pressure engineering (DPE, Fig. 1 a) technique, which can directly induce predominated form I crystals from pure PB-1 melts with low pressure. By optimizing the DPE condition, form I crystals of PB-1 with an initial content of 62.4% was obtained, which can drastically reduce the volume shrinkage ratio. The DPE condition with an optimized Toff value of 0.7s and a cycle number of 120 can achieve the highest content of form I crystals. Only when the Toff value is slightly less than the relaxation time, PB-1 can finally complete the conformational transition from the loose packed (11/3) to the dense packed (3/1) to obtain form I crystals under the DPE condition.